May-Thurner Syndrome in a Patient with Multiple Comorbidities (Revista de Medicina Clinica, 2021)
Background. May-Thurner syndrome, has prevalence of 2% to 3%.  DVTs predominate on  left side, because a compression of the left common iliac vein against the lumbar spine.  Case report.  A 58 years old male with multiple comorbidities, who started with pain and left pelvic member edema, reaching the diagnosis of May Thurner syndrome,  it was solved  by clot lysis and intravenous splint (stent). Conclusion. May-Thurner Syndrome is diagnosed more frequently due to advances in imaging, its presentation may be covered by other clinical and surgical distractors.
Keywords: May-Thyrner sundrome; iliac vein; venous thrombosis; post-thrombosis syndrome; endovascular procedures